Artificial you : AI and the future of your mind - Schneider, Susan, 1968- (Princeton University Press, 2019)
This book discusses what artificial intelligence can truly achieve: Can robots really be conscious? Can we merge with AI, as tech leaders like Elon Musk and Ray Kurzweil suggest? Is the mind just a program? Examining these issues, the author proposes ways we can test for machine consciousness, questions whether consciousness is an unavoidable byproduct of sophisticated intelligence, and considers the overall dangers of creating machine minds.